Hydrothermal Carbonization of Dried Leaves as Adsorbent for Removal of Chloramphenicol compounds. - Kumeren, Isswar Senthil (Universiti Sains Malaysia, 2022)
Water pollution is one of the most inconvenient environmental problems in the world, and it must be addressed. Pharmaceutical industry wastewater contains numerous contaminants, including acidic or caustic dissolved solids, toxic compounds, and other chemicals such as chloramphenicol (CAP). Hydrothermal carbonization (HTC) aid to produce hydrochar by under lower operating conditions in order to increase carbon porosity and decrease production costs. For the removal of CAP from wastewater, dry leaves were hydrothermally carbonised to produce hydrochar. For CAP batch adsorption on resultant hydrochar, various operating parameters, including initial CAP concentration (10 mg/L to 50 mg/L) and solution pH (2 to 10) were utilised. Due to the high driving force for efficient mass transfer, the initial CAP concentration increased the adsorption capacity of the adsorbent. At 35.70 mg/g, the maximum absorption capacity of the hydrochar was reached. The OH group present in hydrochar attach itself to the positive charge of CAP make the basic conditions as opposed to acidic conditions absorbed a greater number of CAP molecules. Based on this study it was found that the Freundlich isotherm and pseudo-second order kinetic models is the suitable experimental data. The rate-controlling step in this adsorption is chemical adsorption. According to the results, hydrochar is a promising adsorbent for the removal of cationic CAP from effluent wastewater.